2010
DOI: 10.2486/indhealth.ms1135
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive Behavioral Therapy Training Using Brief E-mail Sessions in the Workplace: A Controlled Clinical Trial

Abstract: In the present study, we conducted a clinical controlled trial to evaluate the effects of cognitive behavioral therapy (CBT) training in improving depression and self-esteem in workers. A total of 261 workers were assigned to either an intervention group (n=137) or a waiting-list group (n=124). The intervention group was offered participation in a group session with CBT specialists and three e-mail sessions with occupational health care staff. Betweengroup differences in the change in Center for Epidemiologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 22 publications
0
43
1
2
Order By: Relevance
“…In previous studies evaluating the effect of low-intensity CBT, the mean number of CBT sessions ranged from 6 to 7 and showed a high dropout rate during implementation 21) . However, another study using an intervention method similar to that in the present study and conducted in health workers in Japan showed that CBT training using one group session and three e-mail sessions was effective in improving depression with a relatively low dropout rate 19) . In the present study, we asked participants to complete the web-based CBT homework at least three times to ensure feasibility and avoid placing further pressure on busy participants and exacerbating dropout rates.…”
Section: Online Homework Using the Web-based Cbt Programmentioning
confidence: 48%
See 2 more Smart Citations
“…In previous studies evaluating the effect of low-intensity CBT, the mean number of CBT sessions ranged from 6 to 7 and showed a high dropout rate during implementation 21) . However, another study using an intervention method similar to that in the present study and conducted in health workers in Japan showed that CBT training using one group session and three e-mail sessions was effective in improving depression with a relatively low dropout rate 19) . In the present study, we asked participants to complete the web-based CBT homework at least three times to ensure feasibility and avoid placing further pressure on busy participants and exacerbating dropout rates.…”
Section: Online Homework Using the Web-based Cbt Programmentioning
confidence: 48%
“…A possible solution is therefore brief and easy-toimplement CBT including provision of information on CBT via books, group training, telephone, and the Internet in a self-study format. However, while intervention using brief CBT has been reported to reduce depression, anxiety, stress 19,20,25) , and absenteeism 30,31) , to our knowledge, few reports have remarked on intervention via brief CBT to increase positive mental health including work performance, which is of key importance in the workplace. Proudfoot et al (2009) provided CBT training that consisted of 3-hour sessions once a week, for 7 weeks to employees in the sales division of a financial services company and examined their sales after 2 years.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A blended approach was also with a sample of 261 white collar workers in the workplace 23) , in which a 3-h CBT training group was followed by three individualized e-mail sessions (comprising CBT homework exercises and feedback from occupational physicians and nurses). The intervention produced a significant decrease in depressive symptoms compared with controls, as well as enabling the intervention group to significantly improve on self-reported understanding of stress control skills.…”
Section: Resultsmentioning
confidence: 99%
“…The Japanese version of this battery has already been applied in clinical studies. 14 The FAMS consists of seven subscales (mobility, symptoms, emotional well-being, general contentment, thinking/fatigue, family/social well-being and additional concerns) comprising 58 items, with each item scored on a 5point scale ranging from 0 ("not at all") to 4 ("very much"). 15 FAMS was used in our previous study.…”
Section: Assessment Treatment Effects By Cbtmentioning
confidence: 99%